36 Prognostic value and association with veliparib benefit of modeled CA-125 elimination kinetics (KELIM) in patients with newly diagnosed ovarian cancer: analysis from the VELIA/GOG-3005 study. (13th November 2020) - You, B; Fleming, G; Bookman, M; Moore, KN; Steffensen, KD; Coleman, RL
Abstract : Introduction: In VELIA (Phase 3), veliparib with carboplatin/paclitaxel (CP), followed by veliparib maintenance (veliparib-throughout) led to improved progression-free survival (PFS) vs CP alone (control). This exploratory analysis assessed the prognostic and predictive value of the modeled CA-125 elimination rate constant, KELIM. Methods: KELIM was estimated from treatment-related pharmacodynamic modeling of CA-125 values. Median KELIM was used to define favourable (≥median)/unfavourable (<median) KELIM groups. Patients were analyzed by surgery type: primary (PDS) or interval (IDS) debulking surgery. Results: In the IDS population (N=154), patients with favourable KELIM had a higher frequency of complete surgery vs unfavourable KELIM (51.9% vs 32.4%), confirming KELIM as a chemosensitivity marker. In both PDS (N=700) and IDS populations, median PFS was longer with favourable KELIM vs unfavourable KELIM, demonstrating a prognostic value. In the PDS population, median PFS was longer in the veliparib-throughout arm relative to control irrespective of KELIM (29.6 vs. 20.9 and 18.2 vs 15.4 months in favourable and unfavourable KELIM groups, respectively; figure 1 ). In the IDS population, median PFS was longer with veliparib-throughout vs control for patients with favourable KELIM only (29.3 vs 20.8 months; figure 2 ). Conclusion: In VELIA, KELIM was prognostic for PFS and IDS outcomes. Current data suggest KELIM may be associated with veliparib benefit. Ongoing analyses will explore how baseline characteristics contribute to KELIM predictive/prognostic value.